Prolonged Water Deficit Reveals New Profile of Sugarcane Gene Expression and Metabolic Pathway Related to Tolerance - Robiati Telles, Bruna [UNESP]; de Souza Carvalho, Flávia Maria [UNESP]; da Silva Vantini, Juliana [UNESP]; Andrucioli Belesini, Aline [UNESP]; Marques de Castro, Giovanni; Giachetto, Poliana Fernanda; Domingues Carlin, Samira; Ramos da Silva, Thais [UNESP]; Guariz Pinheiro, Daniel [UNESP]; Cazetta, Jairo Osvaldo [UNESP]; Tiraboschi Ferro, Maria Inês [UNESP] (Springer Nature, 2019)
Drought is the abiotic stress that most influences the sugarcane energy production, and has become even more critical after sugarcane cultivation expanded to regions with water scarcity. To overcome this problem, it is necessary to develop and use cultivars that are more adapted to drought stress. The present work analyzed biometrics, physiological behavior and the gene expression profiles of sugarcane subjected to different periods of water deficit simulating field conditions. The cultivars SP81-3250 (drought-tolerant) and RB855453 (drought-sensitive) were cultivated in a greenhouse at three levels of soil–water potential (control, moderate and severe). The biometric, physiological and molecular characteristics of these cultivars were evaluated at 30, 60 and 90 days post-treatment. We found significant differences in the biometric and physiological parameters in response to the treatments. The de novo assembly of the transcriptomes allowed us to identify a total of 5236 genes that were exclusive to either of the two cultivars. We analyzed 2635 genes exclusive to the drought-tolerant cultivar and involved in the response to prolonged water deficit. Some of these genes showed a very interesting expression profile: DNA helicase, NAC proteins, E3 ligase, serine/threonine kinase and proteins of the salicylic acid pathway. This work also identified 39 orphan genes in the drought-tolerant cultivar that can be considered target genes for future studies regarding water stress.
Keywords: De novo assembly; Drought; Exclusive genes; RNA-seq; Saccharum spp